A systematic review of the neural correlates of positive emotions - Leonardo Machado; Amaury Cantilino (Brazilian Journal of Psychiatry)
Objective: To conduct a systematic literature review of human studies reporting neural correlates of positive emotions. Methods: The PubMed and Web of Science databases were searched in January 2016 for scientific papers written in English. No restrictions were placed on year of publication. Results: Twenty-two articles were identified and 12 met the established criteria. Five had been published during the last 4 years. Formation and regulation of positive emotions, including happiness, are associated with significant reductions in activity in the right prefrontal cortex and bilaterally in the temporoparietal cortex, as well as with increased activity in the left prefrontal regions. They are also associated with increased activity in the cingulate gyrus, inferior and middle temporal gyri, amygdalae, and ventral striatum. Conclusion: It is too early to claim that there is an established understanding of the neuroscience of positive emotions and happiness. However, despite overlap in the brain regions involved in the formation and regulation of positive and negative emotions, we can conclude that positive emotions such as happiness activate specific brain regions.